SLC7A5 is required for cancer cell growth under arginine-limited conditions - Kyle N. Dunlap; Austin Bender; Alexis Bowles; Alex J. Bott; Joshua Tay; Allie H. Grossmann; Jared Rutter; Gregory S. Ducker (Cell Reports)
Summary: Tumor cells must optimize metabolite acquisition between synthesis and uptake from a microenvironment characterized by hypoxia, lactate accumulation, and depletion of many amino acids, including arginine. We performed a metabolism-focused functional screen using CRISPR-Cas9 to identify pathways and factors that enable tumor growth in an arginine-depleted environment. Our screen identified the SLC-family transporter SLC7A5 as required for growth, and we hypothesized that this protein functions as a high-affinity citrulline transporter. Using isotope tracing experiments, we show that citrulline uptake and metabolism into arginine are dependent upon expression of SLC7A5. Pharmacological inhibition of SLC7A5 blocks growth under low-arginine conditions across a diverse group of cancer cell lines. Loss of SLC7A5 reduces tumor growth and citrulline import in a mouse tumor model. We identify a conditionally essential role for SLC7A5 in arginine metabolism, and we propose that SLC7A5-targeting therapeutic strategies in cancer may be effective in the context of arginine limitation.